Urachal Carcinomas: A Comprehensive Systematic Review and Meta-analysis - Caio Vinícius Suartz; Lucas Motta Martinez; Marcelo Henrique Lima Silvestre; Richard Dobrucki de Lima; Pedro Henrique Souza Brito; Ketlyn Assunção Galhardo; Roberto Iglesias Lopes; Victor Hondo Silva de Moraes; Caio Mazzonetto Teofilo de Moraes; Luana Covatti; Maria Fernanda Dias Azevedo; Lucas Schenk de Almeida; et al. (International Brazilian Journal of Urology)
ABSTRACT Objective: This systematic review and meta-analysis aim to consolidate current evidence on the diagnosis, epidemiology, and treatment of urachal carcinoma, a rare malignancy with limited data. Materials and Methods: A systematic search of PubMed/MEDLINE was conducted up to September 2024 to identify studies involving patients with urachal carcinoma, reporting clinical epidemiological characteristics, diagnostic strategies, histopathological findings, tumor staging, treatment modalities, and oncological outcomes. Extracted data were systematically synthesized, and statistical analyses, including a single-arm meta-analysis, were performed to comprehensively evaluate oncological outcomes. Results: Our study includes 1,901 cases of urachal carcinoma from 50 studies. The findings support the oncologic advantage of en-bloc resection with umbilectomy in localized disease, demonstrating improved survival outcomes and reduced recurrence rates. In the adjuvant setting, those receiving cisplatin-based therapy presented the best response, with 65.73% with no disease progression; similarly, in the metastatic disease, cisplatin-based regimens seem to have better responses in metastatic disease. The single-arm meta-analysis estimated a 5-year overall survival rate of 51% (95% CI: 0.49–0.54). Tumor recurrence was documented in 35% of cases (95% CI: 0.25–0.45), with local recurrence occurring in 28% (95% CI: 0.18–0.38), with the average time to recurrence of 27.6 months. Conclusion: Our study provides the most comprehensive review of urachal carcinoma to date, providing evidence to guide clinical decisions. It underscores the oncologic benefits of en-bloc resection with umbilectomy and specific chemotherapeutic regimens. Emerging alternative therapies also show potential, highlighting the need for further research to optimize patient outcomes.